Factors Related to Glaucoma Patients at the Main Outpatient Clinic of Medan Eye Center - Siregar, Okkis Razuansyah; Azrial, T. Indra (Newinera Publisher, 2024)
Glaucoma is a condition where eye pressure damage the optic nerve. Usually, high eye pressure will gradually damage the optic nerve fibers, resulting in disruption of the field of vision. Galucoma is the second most common cause of blindness in the world after cataracts. This study aims to determine the factors associated with glaucoma sufferers. The research conducted is analytic in nature with a case control study design that aims to see the relationship of the independent variables. Data obtained from medical records that met the inclusion criteria were 55 medical record data. Because it met the inclusion criteria, all data was used as a researchsample (total sampling). The result of this study show that of the 4 risk factors for glaucoma patients, all have a relantionship of the occurrence of glaucoma. Calculated Chi-Square value with < p=0,05), this shows that there is a significant relationship between risk factors for glaucoma sufferers. It is hoped that every health service center will routinely provide education to patients about the importance of regular eye health checks. In order to be able to detect more quickly if you have early symptoms of eye disorders.